2023
DOI: 10.24425/pjvs.2023.145012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-1,3/1,6 glucan dietary supplements on some immunological and hematological health markersin Siberian sturgeon ( Acipenser baerii) infected with Aeromonas hydrophila

Abstract: This experimental study aimed to investigate some hematological and immunological changes as a result of Aeromanas hydrophila infection in Siberian sturgeon (Acipenser baerii Brandt, 1869). Their feeds were supplemented with β-1,3/1,6 glucan at different ratios, 250 mg/kg (βG 250 ); 500 mg/kg (βG 500 ) and 750 mg/kg (βG 750 ). To create an experimental infection, 4×10 6 cfu/ml Aeromonas hydrophila inoculum was intraperitoneally injected to fish. 0.1 ml intraperitoneal bacteria injection was given to the fish i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Hematological parameters have been important physiological assays for analyzing pathological variations in human and fish species [31,46,47]. Our results showed that high starch increased RBC counts and HGB levels, especially in the D1, D3 and D5 groups, which was in line with former results in Siberian sturgeon (Acipenser baerii) [48]. It is well-known that RBC and HGB undertake key roles in increasing oxygen-carrying, metabolic capacity and redox regulation in humans and animals [49][50][51].…”
Section: Discussionsupporting
confidence: 89%
“…Hematological parameters have been important physiological assays for analyzing pathological variations in human and fish species [31,46,47]. Our results showed that high starch increased RBC counts and HGB levels, especially in the D1, D3 and D5 groups, which was in line with former results in Siberian sturgeon (Acipenser baerii) [48]. It is well-known that RBC and HGB undertake key roles in increasing oxygen-carrying, metabolic capacity and redox regulation in humans and animals [49][50][51].…”
Section: Discussionsupporting
confidence: 89%
“…Toxic agents, e.g., metal ions, pesticides, or other anthropogenic aquatic pollutants, as well as pharmaceuticals such as immunomodulators, antimicrobial and antiparasitic therapeutics, or anesthetics, were proven to cause hematological changes in fish [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. To observe toxicity-induced alterations, it is necessary to provide reference values.…”
Section: Hematological Analysis In Fish Toxicologymentioning
confidence: 99%